Development of Android-Based Modules to Improve Learning Outcomes and Learning Motivation of High School Students - Novi Alisia; Albertus Djoko Lesmono; Yushardi Yushardi (Universitas Lambung Mangkurat, 2022)
Physics is very well known as a difficult science to understand because it contains many complex mathematical formulas and calculations that can affect student learning outcomes and motivation. To overcome this situation, it is necessary to innovate teaching materials, namely with android-based modules. Almost all students now have a smartphone. An android-based physics module was developed to improve student learning outcomes and motivation. This research is a Research and Development (R&D) research using a Nieveen research design which includes 1) preliminary research, 2) the design stage (prototype stage), and 3) the assessment stage. The android-based module was validated by two expert validators who are lecturers of Physics Education at the University of Jember, obtaining the same score of 75 in the valid category. As for the validation results, the user validator, a physics teacher at MA Raudaltul Ulum obtained a score of 92.8 with a very valid category. To find out the increase in student learning outcomes, pre-test and post-test questions were given. The pre-test and post-test results were analyzed using the N-gain test and obtained a score of 0.72 in the high category. Learning motivation is done by distributing questionnaires. The distribution of the questionnaire was carried out after learning using an android-based module.